A Suggested Formula for Postmortem Estimation of Brain Edema Using Morphometric Parameters in Egyptian Population - Abd El-Hai, Amira A; Shokry, Dina A; Elghamry, Hoda; Hassan, Hanan Hosny; Basyoni, Hoda Ahmed; Razik, Heba Abdo Abdel (The American journal of forensic medicine and pathology, 2022)
The purpose of this study was to find a mathematical relation that would be able to determine the existence of brain edema with a certain degree of accuracy, away from the subjective impressions of each examiner. The analyzed study sample consists of 100 brains that underwent forensic autopsy in the Egyptian Forensic Medicine Authority, Zagazig department, from January 2017 to June 2018. Measurements of morphometric parameters of the skull were used to determine the volume and diameters of the cranial cavity. Subjects were divided histologically into 2 groups according to the presence or absence of brain edema. Using this methodological approach, 88% of the brains would be correctly classified as edematous, and 12% would be incorrectly classified as edematous. It was found that the mean ± SD value of brain weight was 1377.1 ± 124.5 g. The mean ± SD value of the brain volume was 1319.7 ± 58.5 cm3. The mean value of brain density was 1.04 ± 0.09 g/dL. It was found that there was a significant difference between subjects with brain edema and those without brain edema regarding measured and estimated brain weight, brain volume, and brain density. There was no statistically significant difference between age and sex regarding brain weight, brain volume, longitudinal diameter, width, and height of the skull. The study results will significantly facilitate the daily routine macroscopic assessment of brain edema based on scientifically determined principles. However, any estimation must still be used with caution and in combination with clinical information and macroscopic and histological findings.